Gasotransmitters: Novel Regulators of Epithelial Na+ Transport? - Althaus, Mike (Frontiers in Physiology, 2012)
The vectorial transport of Na+ across epithelia is crucial for the maintenance of Na+ and water homeostasis in organs such as the kidneys, lung or intestine. Dysregulated Na+ transport processes are associated with various human diseases such as hypertension, the salt-wasting syndrome pseudohypoaldosteronism type 1, pulmonary edema, cystic fibrosis or intestinal disorders, which indicate that a precise regulation of epithelial Na+ transport is essential. Novel regulatory signaling molecules are gasotransmitters. There are currently three known gasotransmitters: nitric oxide (NO), carbon monoxide (CO) and hydrogen sulfide (H2S). These molecules are endogenously produced in mammalian cells by specific enzymes and have been shown to regulate various physiological processes. There is a growing body of evidence, which indicates that gasotransmitters may also regulate Na+ transport across epithelia. This review will summarize the available data concerning NO, CO and H2S dependent regulation of epithelial Na+ transport processes and will discuss whether or not these mediators can be considered as true physiological regulators of epithelial Na+ transport biology.